2014
DOI: 10.1007/978-1-4939-2074-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Immortalized Human Hepatic Cell Lines for In Vitro Testing and Research Purposes

Abstract: SummaryThe ubiquitous shortage of primary human hepatocytes has urged the scientific community to search for alternative cell sources, such as immortalized hepatic cell lines. Over the years, several human hepatic cell lines have been produced, whether or not using a combination of viral oncogenes and human telomerase reverse transcriptase protein. Conditional approaches for hepatocyte immortalization have also been established and allow generation of growth-controlled cell lines. A variety of immortalized hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 137 publications
(146 reference statements)
0
46
0
Order By: Relevance
“…The identification and ectopic expression of viral oncogenes made it possible to "immortalize" post-mitotic cells resulting in their cell cycle reentry and subsequent proliferation (185). Especially the simian virus 40 large T antigen (SV40 Tag), due to its ability to suppress the activity of pRb and p53, has been extensively used to generate lines of permanently immortalized parenchymal mammalian cells (e.g., hepatocytes, neurons, skeletal muscle cells and so forth) that could be used as platform for drug screenings and disease modeling (185)(186)(187)(188).…”
Section: Immortalized Amsmentioning
confidence: 99%
“…The identification and ectopic expression of viral oncogenes made it possible to "immortalize" post-mitotic cells resulting in their cell cycle reentry and subsequent proliferation (185). Especially the simian virus 40 large T antigen (SV40 Tag), due to its ability to suppress the activity of pRb and p53, has been extensively used to generate lines of permanently immortalized parenchymal mammalian cells (e.g., hepatocytes, neurons, skeletal muscle cells and so forth) that could be used as platform for drug screenings and disease modeling (185)(186)(187)(188).…”
Section: Immortalized Amsmentioning
confidence: 99%
“…Due to most immortalized human hepatic cell lines having reduced liverspecific functionality (52), different strategies have been used to counteract this issue, including co-culture systems with primary human hepatocytes and overexpressing liver-enriched transcription factors, CYP450 enzymes, or proliferation inhibitors to increase hepatic functions (52). Immortalized human hepatic cell lines have been successfully used to investigate the life cycle of hepatitis C and B viruses (53)(54)(55)(56), and they act as cellular models of hepatocarcinogenesis (57) and steatosis (58).…”
Section: Immortalized or Transformed Cell Linesmentioning
confidence: 99%
“…It has been demonstrated that with the lack of appropriate levels of CYP expression when compared to PHH, HepG2 cells do not fully represent the phenotype of the in vivo hepatocytes and therefore that the detection of many hepatotoxic compounds utilising the HepG2 cells line is inaccurate, and for non-liver specific toxins this model is ineffectual [63]. It is however still the case that 2D cultures of hepatic-derived cell lines are valuable in the early stages of safety assessments [22] and liver cell lines can still provide a convenient and pragmatic initial tool for early screening and drug safety assessment [64].…”
Section: Hepatic-derived Cell Linesmentioning
confidence: 99%